PROFIL KEMAMPUAN TEKNIK DASAR BOLA VOLI PADA PELAJAR SLTA SEDERAJAT DI KOTA PADANG PANJANG - Asep kurniawan, Asep; Muhammad Sazeli Rifki; Nugroho Susanto; ilham; Marsika sepyanda (Jurnal IKEOR, 2024)
PROFILE OF BASIC VOLLEYBALL TECHNIQUE SKILLS IN EQUIVALENT HIGH SCHOOL STUDENTS IN PADANG PANJANG CITY Abstract: The problem of this research is that the basic volleyball technical skills of high school and equivalent students in Padang Panjang City, including passing, passing, passing and blocking, are still unknown. The purpose of this study is to describe the basic technical skills of high school and similar students in Padang Panjang City in terms of braking, overtaking, overtaking and blocking. This type of research includes quantitative research that uses descriptive analysis techniques. The population of this study consisted of high school students and equivalents from Padang Panjang City who participated in volleyball training, with high school students and equivalents from Padang Panjang City selected as research subjects, composed of SMA 3 Padang Panjang, SMK 2 Padang Panjang and MAN. 3 Padang Panjang with a total of 71 people. The sampling technique uses targeted samples. The sample for this study therefore included 24 people. Data collection includes: smash is measured using the Top/Blow test, forehand is measured using the AAHPER serve accuracy test, serve is measured using the block test. The data analysis technique uses quantitative descriptive statistics, that is, finding values ​​by looking for percentages. Search results; “Overall, the basic volleyball technical skills of high school and equivalent students in Padang City are in the corresponding category.” Keywords : Basic technical ability, volleyball.